A Critical Analysis of Livelihood Security of LivestockFarmers in Tamil Nadu - Pulla, Sireesha; Nallathambi, Vimalrajkumar; Raghavan, Nisha Pankaj; Ponniah, Thilakar (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The study was conducted in the north eastern zone of Tamil Nadu state in Tiruvallur, Kancheepuram, and Villupuram districts. A total of 200 respondents (40 each raising cattle, buffalo, sheep, goat, and pigs) and 40 non-livestock farmers, were selected. A Livelihood Security Index was developed, comprising eight dimensions: food, economic, livestock farming, health, education, socio-psychological, infrastructure, and environmental security. The food security index was found to be medium among most livestock farmers but high for pig farmers, while non-livestock farmers ranged from medium to high. The economic security index was high for cattle, buffalo, goat, and non-livestock farmers, medium for pig farmers, and medium to high for sheep farmers. The farming security index varied from medium to high for cattle, sheep, and non-livestock farmers but was medium for buffalo, goat, and pig farmers. The health security index was high for buffalo, pig, and non-livestock farmers, medium for cattle, and medium to high for sheep and goat farmers. In respect of educational security index, all the livestock farmers were in high category and medium to high for non-livestock farmers. The socio psychological and infrastructure security index ranged from medium to high across all groups. The environmental security index was highest for cattle farmers but lower for goat, pig, and non-livestock farmers. Overall, livelihood security was medium to high for cattle, buffalo, and non-livestock farmers but lower for sheep, goat, and pig farmers. These findings can aid policymakers in designing targeted interventions which will boost the livelihood security of livestock farmers.